(untitled) (Global Journal of Science Frontier Research, 2021)
The study of the growth of african mahogany plants in saline environments is extremely important for the adequate productivity of the crop. This study aimed to evaluate the relative and absolute growth rate of young african mahogany plants, Khaya senegalensis, under saline stress, conducted with nutrient solution. The plants were grown in pots containing washed sand, in a greenhouse. Salinity was established by adding NaCl, with levels of electrical conductivity: 1.0 • 3.38 • 15.14 • 29.90 • 42.61 • 53.60 dS m -1 , in a completely randomized design. The height of the plants was measured with the aid of a graduated ruler, placed parallel to the stem, measuring the height from the neck to the apical bud of the stem. With the height results in mind, the relative and absolute growth rate was evaluated by the relationship between final height, initial height and time period. The results were subjected to analysis of variance, using the F test, for the comparison of means, regression analysis for the quantitative study of the characteristics, using the SISVAR 5.6 statistical program and principal component analysis. In the different treatments with salinity there was no difference in plant height, indicating that the species Khaya senegalensis adapted to changes in electrical conductivity, due in part to the use of nutrient solution.